2005
DOI: 10.1289/ehp.8033
|View full text |Cite
|
Sign up to set email alerts
|

Tubular and Glomerular Kidney Effects in Swedish Women with Low Environmental Cadmium Exposure

Abstract: Cadmium is a well-known nephrotoxic agent in food and tobacco, but the exposure level that is critical for kidney effects in the general population is not defined. Within a population-based women’s health survey in southern Sweden (Women’s Health in the Lund Area, WHILA), we investigated cadmium exposure in relation to tubular and glomerular function, from 1999 through early 2000 in 820 women (71% participation rate) 53–64 years of age. Multiple linear regression showed cadmium in blood (median, 0.38 μg/L) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
239
7
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(279 citation statements)
references
References 36 publications
(55 reference statements)
24
239
7
3
Order By: Relevance
“…In conclusion, the levels of cadmium among the women in this study were moderately high with at least one-third excreting over 2 mg cadmium per gram creatinine and at possible risk of renal damage, especially in combination with diabetes (Buchet et al, 1990;Jarup et al 1998;Hellstrom et al, 2001;Akesson et al, 2005). Although there are limitations in the data, the strength of the associations observed and their ability to address concerns raised by the Elders and women involved, especially for informing their children about turtle and dugong liver and kidney and wild clam consumption, add to the growing body of literature enabling toxicological research to help meet people's information needs about these issues (Kim et al, 1998;Kuhnlein and Chan, 2000;Johansen et al, 2004;Judd et al, 2004).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In conclusion, the levels of cadmium among the women in this study were moderately high with at least one-third excreting over 2 mg cadmium per gram creatinine and at possible risk of renal damage, especially in combination with diabetes (Buchet et al, 1990;Jarup et al 1998;Hellstrom et al, 2001;Akesson et al, 2005). Although there are limitations in the data, the strength of the associations observed and their ability to address concerns raised by the Elders and women involved, especially for informing their children about turtle and dugong liver and kidney and wild clam consumption, add to the growing body of literature enabling toxicological research to help meet people's information needs about these issues (Kim et al, 1998;Kuhnlein and Chan, 2000;Johansen et al, 2004;Judd et al, 2004).…”
Section: Discussionmentioning
confidence: 56%
“…Although the critical effect level was initially estimated at 200 mg/g kidney cortex, recent studies have linked measurable effects on renal tubules at much lower levels (Buchet et al, 1990;Jarup et al, 1998;Jarup et al, 2000;Hellstrom et al, 2001;Akesson et al, 2005). There is a relatively small gap between actual (24 to 42 mg per day globally) and the currently accepted ''safe'' intake of 70 mg per day (or 7 mg/kg body weight per week) (JEFCA, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…CONCLUSIONS -Some previous cross-sectional studies demonstrated that cadmium-induced renal tubular dysfunction was potentiated by diabetes in groups of the general population (3,4). Because of its relatively low prevalence and possible confounding factors in a study of the general population, research within a diabetic population may provide more valuable information concerning the relationship among cadmium exposure, diabetes, and renal dysfunction.…”
Section: Characteristics Of Diabetic Subjectsmentioning
confidence: 93%
“…From some cross-sectional population studies, it was reported that diabetes could augment the risk of cadmiuminduced renal damage, especially tubular dysfunction (3,4). Several experimental studies have demonstrated an increased susceptibility toward cadmium nephrotoxicity (5,6) in spontaneously diabetic mice and hamsters, when compared with normal animals of the same strain.…”
mentioning
confidence: 99%
“…Several experimental studies have demonstrated an increased susceptibility toward Cd nephrotoxicity [26] in spontaneously diabetic mice and hamsters, when compared with normal animals of the same strain. Streptozotocin-induced diabetic rats are more susceptible to Cd nephrotoxicity than are normal rats when they are exposed subchronically to Cd chloride in drinking water [27].…”
Section: Introductionmentioning
confidence: 99%